Genetic diversity of Schima superba populations revealed by ISSR analysis - JIN Ze-xin; LI Jun-min; LI Jian-hui (浙江大学学报. 农业与生命科学版)
Genetic diversity and genetic differentiation of Schima superba were analyzed using inter simple sequence repeat (ISSR) molecular technique. Using 12 primers, ISSR amplification was conducted in 180 individuals from 9 Schima superba populations and 221 polymorphic loci were detected from total 245 loci. The total percentage of polymorphic loci (P) was 90.20%, while that at population level averaged 53.02%. Shannon's Information index (I) and Nei's gene diversity (h) of Schima superba at species level was 0.4548 and 0.3016, respectively. The mean of I and h at population level was 0.2914 and 0.1974, respectively. It indicated that the genetic diversity at species level of Schima superba was relatively high. Analysis of molecular variance (AMOVA) demonstrated that the among-population component accounted for 34.37% of the total variation, while the within-population component accounted for 65.63%. The genetic differentiation coefficient (Gst) among populations was 0.3454. The gene flow among populations was low down to 0.9476. The mean pair-wise genetic distance was 0.1547. Based on the geographic locations, these nine populations could be clustered into three groups using unweighted pair group method with arithmetic mean (UPGMA).